Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To find the value of [tex]\( x \)[/tex] that makes the equation [tex]\((x+7)(x-4) = x^2 + 9x - 28\)[/tex] true, let's solve it step by step:
1. Expand the left-hand side:
[tex]\[ (x+7)(x-4) = x^2 - 4x + 7x - 28 \][/tex]
2. Simplify the expression on the left-hand side:
[tex]\[ x^2 - 4x + 7x - 28 = x^2 + 3x - 28 \][/tex]
3. Compare the simplified left-hand side to the right-hand side:
[tex]\[ x^2 + 3x - 28 = x^2 + 9x - 28 \][/tex]
4. Set up the equation by equating the corresponding terms:
[tex]\[ x^2 + 3x - 28 = x^2 + 9x - 28 \][/tex]
5. Since [tex]\( x^2 \)[/tex] and [tex]\(-28\)[/tex] terms cancel out, we are left with:
[tex]\[ 3x = 9x \][/tex]
6. Subtract [tex]\( 3x \)[/tex] from both sides to isolate [tex]\( x \)[/tex]:
[tex]\[ 3x - 3x = 9x - 3x \implies 0 = 6x \implies x = 0 \][/tex]
Therefore, the value of [tex]\( x \)[/tex] that makes the equation [tex]\((x+7)(x-4) = x^2 + 9x - 28\)[/tex] true is [tex]\( \boxed{0} \)[/tex]. Since [tex]\( 0 \)[/tex] is not listed among the provided options (−11, −3, 3, 11), there seems to be an error in the provided options. The correct answer is [tex]\( 0 \)[/tex].
1. Expand the left-hand side:
[tex]\[ (x+7)(x-4) = x^2 - 4x + 7x - 28 \][/tex]
2. Simplify the expression on the left-hand side:
[tex]\[ x^2 - 4x + 7x - 28 = x^2 + 3x - 28 \][/tex]
3. Compare the simplified left-hand side to the right-hand side:
[tex]\[ x^2 + 3x - 28 = x^2 + 9x - 28 \][/tex]
4. Set up the equation by equating the corresponding terms:
[tex]\[ x^2 + 3x - 28 = x^2 + 9x - 28 \][/tex]
5. Since [tex]\( x^2 \)[/tex] and [tex]\(-28\)[/tex] terms cancel out, we are left with:
[tex]\[ 3x = 9x \][/tex]
6. Subtract [tex]\( 3x \)[/tex] from both sides to isolate [tex]\( x \)[/tex]:
[tex]\[ 3x - 3x = 9x - 3x \implies 0 = 6x \implies x = 0 \][/tex]
Therefore, the value of [tex]\( x \)[/tex] that makes the equation [tex]\((x+7)(x-4) = x^2 + 9x - 28\)[/tex] true is [tex]\( \boxed{0} \)[/tex]. Since [tex]\( 0 \)[/tex] is not listed among the provided options (−11, −3, 3, 11), there seems to be an error in the provided options. The correct answer is [tex]\( 0 \)[/tex].
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.